Comorbid internalizing and disruptive behavior disorder in adolescents: offending, trauma, and clinical characteristics - Hoeve, Machteld (Criminal justice and behavior, 2015)
This study examined differences between comorbid internalizing and disruptive behavior disorder (DBD), and those with either internalizing disorder or DBD. We focused on differences with regard to trauma exposure and offending characteristics in 8,431 juvenile justice youths. Self-reported, structured interview and official record data were used. Multinomial logistic regression analysis predicted disorder profile from traumatic exposure, suicide attempt, and offending characteristics, adjusting for background variables. Victimization by non-sexual violence was significantly higher in comorbid than in internalizing youth. Also, the number of DBDs, as well as rates of victimization via sexual and non-sexual assault, was significantly higher in the comorbid than in the DBD group. We conclude that a history of victimization, but not an early onset of criminal behavior, was associated with comorbid internalizing disorder and DBD. Findings emphasize the need for improving identification of this comorbid condition and referral for effective treatment.